Association of arterial blood pressure and CPR quality in a child using three different compression techniques, a case report - Sainio, Marko (BioMed Central, 2013)
A 2-year-old boy found in cardiac arrest secondary to drowning received standard CPR for 35 minutes and was transported to a tertiary hospital for rewarming from hypothermia. Chest compressions in hospital were started using two-thumb encircling hands technique. Subsequently two-thumbs direct sternal compression technique and after sternal force/depth sensor placement, chest compression with classic one-hand technique were done. By using CPR recording/feedback defibrillator, quantitative CPR quality data and invasive arterial pressures were available for analyses for 5 hours and 35 minutes. 316 compressions with the two-thumb encircling hands technique provided a mean (SD) systolic arterial pressure (SAP) of 24 (4) mmHg, mean arterial pressure (MAP) 18 (3) and diastolic arterial pressure (DAP) of 15 (3) mmHg. ~6000 compressions with the two thumbs direct compression technique created a mean SAP of 45 (7) mmHg, MAP 35 (4) mmHg and DAP of 30 (3) mmHg. ~20,000 compressions with the sternal accelerometer in place produced SAP 50 (10) mmHg, MAP 32 (5) mmHg and DAP 24 (4) mmHg. Restoration of spontaneous circulation (ROSC) was achieved at the point when the child achieved normothermia by using peritoneal dialysis. Unfortunately, the child died ten hours after ROSC without any signs of neurological recovery. This case demonstrates improved hemodynamic parameters with classic one-handed technique with real-time quantitative quality of CPR feedback compared to either the two-thumbs encircling hands or two-thumbs direct sternal compression techniques. We speculate that the improved arterial pressures were related to improved chest compression depth when a real-time CPR recording/feedback device was deployed. TRIAL REGISTRATION: ClinicalTrials.gov: NCT00951704.